2018
DOI: 10.1021/acs.macromol.7b02514
|View full text |Cite
|
Sign up to set email alerts
|

Surface Aligned Main-Chain Liquid Crystalline Elastomers: Tailored Properties by the Choice of Amine Chain Extenders

Abstract: A promising way to induce shape transformation in soft materials is via spatial variation in the orientation of the alignment of liquid crystalline elastomers (LCEs). Here, we improve the nascent thermomechanial shape transformation in main-chain LCEs prepared via aza-Michael addition reactions. Specifically, increasing the alkyl length in the n-alkylamine chain extender effectively reduces the actuation temperature by destabilizing the nematic phase as well as reduces the glass transition temperature (T g ) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 45 publications
(63 reference statements)
4
66
0
Order By: Relevance
“…The thermomechanical response of these LCE was examined between 25 and 270 °C (Figure S5, Supporting Information). Actuation of the LCEs is again distinguished from the CnM‐CTA LCE chemistries, which actuate gradually across a wide, relatively low temperature range . In the epoxy‐based LCEs, only 5% strain for all spacer lengths is evident up to 200 °C, followed by a rapid shape change between 200 and 250 °C that results in 20% average strain perpendicular to the director and 40% average strain parallel to the director (Figure e, left).…”
Section: Resultsmentioning
confidence: 97%
“…The thermomechanical response of these LCE was examined between 25 and 270 °C (Figure S5, Supporting Information). Actuation of the LCEs is again distinguished from the CnM‐CTA LCE chemistries, which actuate gradually across a wide, relatively low temperature range . In the epoxy‐based LCEs, only 5% strain for all spacer lengths is evident up to 200 °C, followed by a rapid shape change between 200 and 250 °C that results in 20% average strain perpendicular to the director and 40% average strain parallel to the director (Figure e, left).…”
Section: Resultsmentioning
confidence: 97%
“…The procedure of Ahn and co‐workers [ 50 ] was followed with slight modification. RM82, dodecylamine, and 8‐amino‐1‐octanol were combined in a molar ratio of 1.1:0.5:0.5 with 2.5 wt% of Irgacure 651 in a vial and melted at ≈85 °C and vortexed repeatedly.…”
Section: Methodsmentioning
confidence: 99%
“…To fabricate monodomain LCEs, 50 µm thick planar nematic films are synthesized following the work of Ahn and co‐workers (Scheme S1, Supporting Information). [ 50 ] This chemistry is employed due to its amenability to formation of monodomain samples with relatively low nematic‐isotropic transition temperatures ( T NI ) and large thermomechanical strains. Briefly, n ‐dodecylamine and 8‐amino‐1‐octanol are mixed in a 1:1 molar ratio with the diacrylate mesogen RM82 with an overall stoichiometry of acrylate:amine functionalities of 1.1:1, selected to afford a cross‐link density that allows for large strains while maintaining sufficient mechanical robustness.…”
Section: Figurementioning
confidence: 99%
“…More recently, extensive studies on LCE synthesis have been reported based on diacrylate-, divinyl-, or diglycidyl-functionalized LC monomers (so-called reactive mesogens). These monomers can first be chain-extended using alkyl dithiols [19][20][21][22][23][24][25][26][27][28], alkyl amines [29][30][31], or alkyl dicarboxylic acids [32,33], and then they can be crosslinked in the presence or absence of multifunctional crosslinkers to obtain main-chain LCEs. One of the major advantages of the above-mentioned method is that various LC alignment methods can be integrated during LCE synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…As separately demonstrated by the research groups of Ware [37] and Yakacki [38], crystallizable LCEs not only increase the mechanical properties, including stiffness and toughness, but also enhance the blocking stress and work capacity of thiol-acrylate LCEs. Recently, our group also reported that the glass transition temperature and mechanical properties of main-chain LCEs can be effectively manipulated by adjusting the length of the alkyl groups in the primary amine chain extenders, which can systematically alter the actuation temperature [30]. Based on interpenetrating LCE architectures, Yang et al achieved enormous blocking stress (2.53 MPa) and work capacity (1267.7 kJ/m 3 ), which are 7 and 31 times larger than those of skeletal muscles (0.35 MPa and 40 kJ/m 3 ), respectively.…”
Section: Introductionmentioning
confidence: 99%